Contemporary Surgical Trends in the Management of Symptomatic Meniscal Tears among United States Military Servicemembers from 2010 to 2015 - Pekari, Timothy B.; Wang, Kevin C.; Cotter, Eric J.; Kusnezov, Nicholas; Waterman, Brian R. (The Journal of Knee Surgery, 2019)
The purpose of this investigation is to report on trends over time in the treatment of meniscal pathology among military orthopaedic surgeons, as well as to evaluate the impact of patient demographics and concomitant procedure on the type of meniscal procedure performed. We performed a retrospective analysis of all active-duty United States military servicemembers who underwent a meniscal procedure from 2010 to 2015 within the Military Health System. Patient demographics and surgical variables were extracted from the electronic medical record. Treatments were categorized by location and by type of intervention (i.e., repair or debridement). Chi-square and linear regression analyses were performed to identify temporal trends in meniscal procedures and factors that were correlated with the type of meniscal procedure performed. Out of 29,571 meniscal procedures analyzed, partial meniscectomy was performed in 81.3% (n = 24,343) of cases, meniscal repair in 20.3% (n = 6,073), and meniscus allograft transplantation (MAT) in 0.7% (n = 206). The rates of debridement, repair, and concomitant surgeries did not demonstrate any significant temporal trends, whereas MAT demonstrated a significant decrease in overall utilization. Nearly two-thirds of all meniscal procedures were performed in the medial compartment. MAT occurred equally between the medial and lateral compartments. Lateral meniscal lesions demonstrated significantly higher rates of debridement. With each year of advancing age, there was a 3.7% increasing likelihood of meniscectomy and 6.5% decreasing likelihood of repair. Females were more likely to undergo meniscal repair than males. Patients in the military population were more likely to undergo meniscal repair compared with previously reported rates in the civilian population. In this physically active cohort of nearly 30,000 military patients, 1 in 5 meniscal tears were treated with meniscal repair. Meniscal repairs were performed at a higher rate for all age groups compared with previously reported rates in the civilian population. Further research is required to elucidate the causative factors behind these differences and the effect on postoperative outcomes.Level of Evidence: IV, cross-sectional study.
Keywords: meniscus; military; meniscectomy; repair; ACL